Cotton Defense Induction Patterns Under Spatially, Temporally and Quantitatively Varying Herbivory Levels - Eisenring, Michael; Meissle, Michael; Hagenbucher, Steffen; Naranjo, Steven E.; Wettstein, Felix; Romeis, Jörg (Frontiers in Plant Science, 2017)
In its defense against herbivores, cotton (Gossypium spp.) relies in part on a set of inducible, non-volatile terpenoids. Under static damage levels, in-planta allocation of induced cotton terpenoids has been found to be highest in youngest leaves, supporting assumptions of the optimal defense theory (ODT) which predicts that plants allocate defense compounds to tissues depending on their value and the likelihood of herbivore attack. However, our knowledge is limited on how varying, and thus more realistic, damage levels might affect cotton defense organization. We hypothesized that the allocation of terpenoids and densities of terpenoid storing glands in leaves aligns with assumptions of the ODT even when plants are subjected to temporally, spatially and quantitatively varying caterpillar (Heliothis virescens) damage. As expected, cotton plants allocated most of their defenses to their youngest leaves regardless of damage location. However, defense induction in older leaves varied with damage location. For at least 14 days after damage treatments ended, plants reallocated defense resources from previously young leaves to newly developed leaves. Furthermore, we observed a positive hyperbolic relationship between leaf damage area and both terpenoid concentrations and gland densities, indicating that cotton plants are able to fine-tune defense allocation. Although it appears that factors like vascular constraints and chemical properties of individual defense compounds can affect defense levels, our results overall demonstrate that induced defense organization of cotton subjected to varying damage treatments is in alignment with key assumptions of the ODT.